2022
DOI: 10.3390/microorganisms10030611
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Plasmid AmpC Type Resistances in Escherichia coli and Klebsiella pneumoniae and Preliminary Proposal of a Simplified Screening Method for ampC

Abstract: Beta-lactamase (BL) production is a major public health problem. Although not the most frequent AmpC type, AmpC-BL is increasingly isolated, especially plasmid AmpC-BL (pAmpC-BL). The objective of this study was to review information published to date on pAmpC-BL in Escherichia coli and Klebsiella pneumoniae, and on the epidemiology and detection methods used by clinical microbiology laboratories, by performing a systematic review using the MEDLINE PubMed database. The predictive capacity of a screening method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 134 publications
3
22
0
Order By: Relevance
“…Cefoxitin screening however helps to eliminate unnecessary tests which is important for resource limited settings. Thus far, there are several confirmatory phenotypic tests for detection including Disc Potentiation Test, Double Disc Synergy Test, AmpC Disc Test, Disc Approximation Test (DAT), along with the incorporation of inhibitors such as boronic acid or cloxacillin ( Rodríguez-Guerrero et al., 2022 ). The cefoxitin screened isolates in our study underwent DAT and four had inconclusive results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cefoxitin screening however helps to eliminate unnecessary tests which is important for resource limited settings. Thus far, there are several confirmatory phenotypic tests for detection including Disc Potentiation Test, Double Disc Synergy Test, AmpC Disc Test, Disc Approximation Test (DAT), along with the incorporation of inhibitors such as boronic acid or cloxacillin ( Rodríguez-Guerrero et al., 2022 ). The cefoxitin screened isolates in our study underwent DAT and four had inconclusive results.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review identified an increase in the worldwide prevalence of pAmpC BLs in the Gram negative organisms Escherichia coli and Klebsiella pneumoniae over the past ten years ( Rodríguez-Guerrero et al., 2022 ). However data from the Caribbean was not represented in this study ( Rodríguez-Guerrero et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous treatment with third-generation cephalosporins was the only independent risk factor (p=0.008). A similar study found the use of antibiotics containing oxyimino ring for K. pneumoniae strains as a risk factor for ESBL production [25,26]. According to one view, the reason for the differences in terms of risk factors in other studies, as in our study, is; The retrospective character of the study is seen as insufficient number of patients, lack of consensus in distinguishing colonization from real infection, insufficient data on antibiotic use of patients before admission to hospital or infection, and isolates were collected only from certain services [27].…”
Section: Discussionmentioning
confidence: 76%
“…However, there is increasing interest in a group of Enterobacteriaceae responsible for 10% of nosocomial and community UTIs, known as the CESPM group ( Citrobacter freundii , Klebsiella aerogenes , Enterobacter cloacae , Serratia marcescens , Providencia stuartii , and Morganella morganii ). They are characterized by naturally producing chromosomal AmpC-inducible beta-lactamases [ 6 , 7 , 8 ], unlike Enterobacteriaceae which produce plasmid-origin AmpC beta-lactamases, for which various diagnostic methods are available [ 9 ].…”
Section: Introductionmentioning
confidence: 99%